Building Coalitions with NGOs: Religion Scholars and Disability Justice Activism - Iozzio, Mary Jo (Religions, 2018)
The World Council of Churches (WCC), an organization of 348 member churches, is a model of coalition building particularly through its support of individuals, churches, and their ministries for the inclusion, participation, and contributions of people with disabilities in its ecumenical work. The Ecumenical Disability Advocates Network (EDAN) informs one of the initiatives of the WCCfaith in Jesus Christ and communion fellowshipin the journey toward visible unity and justice for people who were too often missing the banquet of a church of all and for all. EDAN and other international disability advocates have most recently embedded its agenda of inclusion into the United Nations Sustainable Development Goals. The United Nations explicitly recognizes the Human Rights for persons with disabilities and, with the Convention of the Rights of Persons with Disabilities (2006), has raised protections against discrimination, exploitation, and abuse of people with disabilities to the level of international law. The World Health Organization works collaboratively in gathering data and local analyses of efforts to minimize preventable disability and maximize rehabilitation program availability with partners across the globe. These organizations, global in nature, have benefitted from the insights raised by people with disabilities and scholars working at the intersections of disability, religion, and justice. This essay examines the efficacy and opportunities of international coalitions available with these organizations so as to challenge the ethics of simple accommodations with a more robust social justice of affirmation and advocacy for people with disabilities: a new paradigm for our churches and our world.